Poland’s population policy during the COVID-19 pandemic - Szymborski, Janusz (Journal of Health Inequalities, 2021)
The aim of this study is to initiate a discussion on the directions of research on the impact of the pandemic on demographic processes in Poland. Due to the dramatic increase in the number of deaths in 2020, the focus is on one of the four main goals of Poland’s population policy, namely to improve the health of the population and reduce mortality. Some have argued that the unfavourable course of the pandemic in Poland is mainly determined by two factors: the poor health condition of the population as a result of many years of neglect of disease prevention and risk factors, and persistent weaknesses in the functioning of the healthcare system. Therefore, this paper proposes a list of research problems in the field of public health that need to be urgently addressed. Particular emphasis is placed on a syndemic approach (infections, chronic diseases, socioecological factors), as well as health education, prevention of infectious diseases, legislative measures, the social dimension of health, and interdisciplinary cooperation.